EVALUASI PENGENDALIAN INTERN ATAS SISTEM DAN PROSEDUR PENGELOLAAN KARTU AUTOMATIC TELLER MACHINE - Pranata, Berry Prima (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze the implementation of internal control system and evaluation to the system and management procedure of automatic teller card. The research method in this research is carried out by using descriptive, which is describing and explaining the observation of subject problem at BCA Branch of Wholesale Shopping Center Branch (BCA-PGS), and comparing between the fact found in the practice with standard of internal control system of General Bank (Bank of Indonesia: 2013) as well as the system evaluation and management procedure of ATM card. The analysis result shows that internal control system which is implemented at BCA-PGS has been running well in accordance with standard; nevertheless it needs improvement in the filling out forms to make it more informative and employeesâ competency with the education improvement, as well as system and management procedure of ATM card which has been in accordance to the standard.Keywords: Internal Control System, ATM Card.